Atopic dermatitis - pathogenesis, types, differentiation, prevention, treatment - Wilczyńska, Barbara; Grzybek, Monika; Kasprzak, Anna; Kułaga, Monika; Mazur-Lesińska, Diana; Szostak, Barbara; Wielgosz-Biała, Sylwia; Tyszkiewicz, Krzysztof; Kasprzak, Małgorzata; Łozowski, Borys (Journal of Education, Health and Sport, 2025)
Atopic dermatitis (AD), defined according to the current World Health Organisation (WHO, 1990) nomenclature as eczema, is a chronic, recurrent, inflammatory skin disease, usually beginning in early childhood, characterised by severe pruritus, typical localisation, characteristic lesion morphology, and very - often coexisting with other atopic diseases. Atopic dermatitis is strongly associated with allergic respiratory diseases such as asthma and allergic rhinitis, hence the name "allergic triad". There has been a significant increase in the incidence over the past 25 years, with the number of diagnosed cases of the condition increasing more than twofold and even more in some countries. There is a wide variation in prevalence of 1% and 20% between countries, with the most recent data indicating that the disease has reached a certain in English-speaking countries and affects 20% of the population. The increase in the prevalence of AD, is likely to be influenced by negative environmental changes, such as climate, exposure to second-hand smoke, major industrialisation and the consequent increase in air and food pollution and food pollution, as well as the consumption of highly processed fast food. This issue requires further research, with particular attention to infancy and early childhood, when the immune system is maturing. These factors, as well as certain environmental allergens, have a strong influence on the onset of the first symptoms associated with the disease, as well as its course.